Relationship Between Parity and Exclusive Breastfeeding in Breastfeeding Mothers - Putri Ifada, Loladianis; Atik Maryanti, Syska; Bachri, Syaiful (Universitas Bondowoso, 2023)
Introduction: Based on data by Indonesia’s Minister of Health, the coverage of exclusive breastfeeding has decreased from 2018 – 2020 which is the coverage reach 66,06%. This coverage didn’t fulfill the target set by Minister of Health, aiming 80% coverage of exclusive breastfeeding. Factors associated with this matter, one of them is parity. This study aims to determine the relationship of parity with exclusive breastfeeding practice. Methods: The study used is a literature study with the type of Systematic Mapping Study. The articles were taken from the Google Scholar and Microsoft Academic databases which obtained a total 319 articles, then were screened using PEOS framework and based on with inclussion and exclussion criteria researcher succeed to earn ten final articles consisting seven national articles and tree international article. Results: The results of the analysis of 10 articles show that the majority of respondents are multipara mother which is 55%-62%, the majority of respondents gave exclusive breastfeeding to their babies which is 52,5%-69,8% and all articles shows p-value < α which means there is relationship between parity and exclusive breastfeeding practice. Discussion: Parity is a factor of exclusive breastfeeding practice. Health provider should give informations related to the benefit of exclusive breastfeeding to boost mother’s knowledge about the importance of exclusive breastfeeding practice.